The reform'd coquet ; or, Memoirs of Amoranda : familiar letters betwixt a gentleman and a lady ; and, the accomplish'd rake, or, Modern fine gentleman - Davys, Mary, 1674-1731 (Eighteenth-century novels by women., 1999)
The Reform'd Coquette (1724) tells the story of Amoranda, a good but flighty young woman whose tendency toward careless behavior is finally tamed. Familiar Letters Betwixt a Gentleman and a Lady (1725), a satire of both political debate and women's place in society, portrays a Tory man and a Whig woman who find themselves discussing love, even though they have pledged to remain platonic friends. The Accomplish'd Rake (1727) follows the exploits of Sir John Galliard from youth to manhood, when he is forced to accept responsibility for his actions. Mary Davys (1674?-1732) was one of the earli.